EFFECT OF AUTOLOGOUS PLATELET-RICH PLASMA ON ARRANGEMENT OF COLLAGEN FIBERS AT INJURED ACHILLES TENDON ENTHESES IN RABBITS - Tayyaba Faisal (Army Medical College Rawalpindi, 2019)
Objective: To evaluate the effects of autologous platelet-rich plasma on arrangement of collagen fibers at injured Achilles tendon entheses in rabbits.